Potential anti-inflammatory, anti-ulcerogenic and antioxidant activity of Nasturtium officinalis water extract - Fares, N. (2010)
Nasturtium officinalis is a widely used edible plant in the Mediterranean region and well known for its medicinal value in folk medicine. The present study explores the effects of the water extract of N. officinalis upon rat blood lipid profile, glycemia, liver enzymes, gastric ulcer, inflammation and antioxidant activities. One month of aqueous plant extract intake (100, 250 and 500mg/kg body weight) via drinking water, showed no significant changes in the serum lipids and glucose level. Liver enzyme activities (AL T, ALP, AST) were not negatively affected thus assuring that the extract has no hepatotoxic effects over the study period. Doses of 100, 250, and 500mg/kg body weight exhibited substantial anti-inflammatory effects against carrageenan induced inflammation (60.0, 51.1 and 46.11%) compared to 73.33% for diclofenac [1]. Similar doses caused respectively 4.7, 51.5 and 57.1% anti-inflammatory effects against formalin induced inflammation [2]. For the anti-ulcerogenic activity, pre-treatment of fasted rats with100 and 250mg/kg body weight demonstrated significant protection (32.1% and 51% respectively) against ethanol-induced gastric ulcer, compared to 10mg/kg cimetidine (50.24%) and 3mg/kg omeprazole (47.81%)3. The extract also exhibited a strong scavenging activity against DPPH radicals (55%)4. In conclusion, our data demonstrates the beneficial anti-ulerogenic, anti-inflammatory and antioxidant activities of Nasturtium officinalis.